Customer satisfaction as benchmark for contract catering performance within the Army Basic Recruit Training Centre (PUSASDA) - Abdullah, Nurhazwani; Abdullah, Siti Syazwani; Ghazali, Hazrina (2013)
Customer satisfaction has been given much attention in the measurement of business performance of the institutional foodservices for the food and services. This study examines the army recruits’ satisfaction with Acute Care Hospital Foodservice Patient Satisfaction Questionnaire (ACHFPSQ). This survey was part of the menu intervention study and implemented in three dining halls in the Army Basic Recruit Training Centre with involvement of fifty male army recruits. Customer satisfaction was assessed after six months of staying within the training centre. Main outcome measured were the scores of foodservice dimensions and overall satisfaction. Relationship between foodservice dimensions with overall satisfaction was assessed with Multiple Linear Regression Analysis. Findings revealed that the army recruits rated the highest score for meal service quality (score 2.81) while the lowest score was for physical environment (score 2.58). Overall score of foodservice satisfaction was 2.48, indicated that the army recruits had poor satisfaction level of the catering. The regression analyses revealed that staff and service issues was the only significant predictor positively related to the army recruits’ overall foodservice satisfaction. Further approach to improve the army recruits’ satisfaction with the food and services are warranted.